2015
DOI: 10.7202/1027979ar
|View full text |Cite
|
Sign up to set email alerts
|

Genre et prise de décision au sein du ménage au Burkina Faso

Abstract: L’étude examine les facteurs sociodémographiques et économiques qui influencent la participation des femmes à la prise de décision au sein du ménage au Burkina Faso. Les données de l’Enquête démographique et de santé réalisée en 2010 sont exploitées à l’aide d’une régression logistique. Ces données quantitatives sont complétées par des entretiens qualitatifs réalisés en 2011 sur le thème « genre et décision économique au Burkina Faso ». Les résultats montrent que les femmes participent peu aux décisions concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…In the context of poverty, women's paid work should enable them to improve their negotiating and bargaining positions within the household. Bilampoa (2014) reinforces this viewpoint, stating that paid work is one of the factors that promote women's participation in decisionmaking within Burkinabe households. Studies by Acharya et al (2010) and Becker (1985) support this perspective, showing that employed women are more likely to participate in household decision-making than unemployed women, thanks to the income generated by their employment.…”
Section: Literature Reviewmentioning
confidence: 82%
See 2 more Smart Citations
“…In the context of poverty, women's paid work should enable them to improve their negotiating and bargaining positions within the household. Bilampoa (2014) reinforces this viewpoint, stating that paid work is one of the factors that promote women's participation in decisionmaking within Burkinabe households. Studies by Acharya et al (2010) and Becker (1985) support this perspective, showing that employed women are more likely to participate in household decision-making than unemployed women, thanks to the income generated by their employment.…”
Section: Literature Reviewmentioning
confidence: 82%
“…For Lemieux and Mercier (1989), a member's contribution to the household income increases their decision-making power within the household, particularly if they become the main provider. Several authors have confirmed these results by finding that contribution to household income influences the level of control and power in household financial decision-making, particularly for the wife (Lee and Beatty 2002;Burgoyne and Morison 1997;Goode et al 1998;Pahl, 1995Pahl, , 2000Pahl 1993, 1994;Yilmazer and Lyons 2010;Bilampoa, 2014).…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…Elle donne libre champ aux personnes d'accepter les débats contradictoires, à condition de s'excuser avant le début de la discussion (Berthe, 2013). Cette façon de mener la recherche m'a permis d'aborder certains sujets plus délicats tels que les divisions des rôles dans la famille, les pratiques matrimoniales ou de gestion dans la famille et d'accès aux ressources, et la contribution des femmes aux dépenses familiales (Attané, 2009;Gnoumou Thiombiano, 2014;Kobiané, 2007). Toutefois, la réflexion qu'une présidente d'une association de femmes entrepreneures m'a faite à la fin d'une séance d'entretien de groupe m'a conduit à ajuster ma stratégie de recherche.…”
Section: Les Entretiens De Groupe Et L'observation Participante Commeunclassified
“…En effet, « des études de cas réalisées dans les pays voisins (Clark, 1994 ;Vaa, 1991 ;Roberston, 1984 ;Etienne, 1983) tendent à montrer que la situation des femmes se dégrade dans le contexte urbain actuel (…) les ménages s'appauvrissent et comme il revient ultimement aux femmes de s'occuper des enfants, elles sont contraintes de prendre en charge une part de plus en plus importante du budget familial en dépit de leurs maigres moyens » (Le Jeune, 2007, p. 192). Par ailleurs, plus les femmes mariées burkinabè sont instruites, travaillent, vivent en milieu urbain, plus elles bénéficient d'autonomie dans les décisions de se déplacer (Thiombiano, 2014). Au-delà de ces facteurs, des migrantes surtout urbaines dont l'époux est absent se démarquent de la « figure de Pénélope » (Boyer, 2013) que leur impose la tradition.…”
Section: Méthodologieunclassified